Product and Brand as Determinant Factors in Customer Purchase Decision in Kota Kinabalu - Sidah Idris; Shivarungini a/p S. Peachamtuhu; Wajiran@ Wajiran Sinun (2018)
Today consumers intend to make their decisions based on the product and a brand influences from individual to make their purchase decisions. The aim of this study is to know about the variables of product and brand as determinant factors towards customer’s purchase decision. Besides that, there were 140 respondents were involved in this survey where the questionnaires are distributed by hand in this research. This sample size was measured by using the G-Power. This study tested the hypothesis and model with SmartPLS3. The findings of this study showed that purchase decision has significantly influenced by price and loyalty towards the product and brand purchased whereas quality and trust are not significant. There are many other external factors that can influence the customers’ purchase decision. In addition, this, there are no indirect relationship involved in this research. Managerial implications and future directions are also discussed in this study.